An extraskeletal Ewing's sarcoma: a challenging diagnosis with several approaches in a young woman - Carolina Souza-de Oliveira; Isabella C. Mendes-Alexandre; Laísa Ezaguy-de Hollanda; Rebeca de Oliveira-; Vanessa Ribeiro-Ferreira; João V. Chagas-Rossin; Hitesh Babani; Patricia Chicre-Ba; Luciana Mendes-dos Santos (Sociedade Portuguesa de Dermatologia e Venereologia, 2024)
Extraskeletal Ewing's sarcoma is an unusual primary tumor of the deep soft tissues. Clinically, skin lesions are usually fastgrowing and aggressive, with a risk of metastasis, and are more common in the paravertebral region and lower limbs. The ultimate diagnosis is made by anatomopathological study. This report describes the case of a 21-year-old patient with a tumor on her right flank that had been present for the past 2 months. She underwent surgery in an emergency department and progressively became more ill.